A bone‐on‐a‐chip collagen hydrogel‐based model using pre‐differentiated adipose‐derived stem cells for personalized bone tissue engineering. Issue 1 (7th October 2022) - Alamán‐Díez, Pilar; García‐Gareta, Elena; Arruebo, Manuel; Pérez, María Ángeles
Abstract: Mesenchymal stem cells have contributed to the continuous progress of tissue engineering and regenerative medicine. Adipose‐derived stem cells (ADSC) possess many advantages compared to other origins including easy tissue harvesting, self‐renewal potential, and fast population doubling time. As multipotent cells, they can differentiate into osteoblastic cell linages. In vitro bone models are needed to carry out an initial safety assessment in the study of novel bone regeneration therapies. We hypothesized that 3D bone‐on‐a‐chip models containing ADSC could closely recreate the physiological bone microenvironment and promote differentiation. They represent an intermedium step between traditional 2D–in vitro and in vivo experiments facilitating the screening of therapeutic molecules while saving resources. Herein, we have differentiated ADSC for 7 and 14 days and used them to fabricate in vitro bone models by embedding the pre‐differentiated cells in a 3D collagen matrix placed in a microfluidic chip. Osteogenic markers such as alkaline phosphatase activity, calcium mineralization, changes on cell morphology, and expression of specific proteins (bone sialoprotein 2, dentin matrix acidic phosphoprotein‐1, and osteocalcin) were evaluated to determine cell differentiation potential and evolution. This is the first miniaturized 3D‐in vitro bone model created from pre‐differentiated ADSC embedded in a hydrogel collagen matrix which could be used for personalized bone tissue engineering.